Expanding distribution and occurence of the Indo-Pacific Stomatopod, Erugosquilla massavensis (Kossmann, 1880) on the Aegean coast of Turkey - OZCAN, T.; ATES, A.S.; KATAGAN, T. (Mediterranean Marine Science, 2008)
The indo-Pacific mantis shrimp, Erugosquilla massavensis was recently collected from Sigacik Bay, located on the Aegean coast of Turkey. It is the first record of the species along the Aegean coast of Turkey